Perilaku Literasi Digital Keagamaan Mahasiswa UIN Sunan Ampel Surabaya - Rizki Ramdhani; Indri Sudanawati Rozas; Evi Fatimatur Rusydiyah (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
State Islamic University of Sunan Ampel Surabaya (UINSA) implements integrated twin-towers learning model that combines Islamic scholarship with science, technology, social, and humanities. Through this learning model, the students of UINSA get courses on strengthening Islamic values regardless of their study program. Students are required to be independent in learning, including getting religious learning resources that can be accessed via the internet. However, religious information circulating on the internet is not always true and valid, so it affects on student behavior in accessing religious literacy in the digital world. This article aims to describe the level of religious digital literacy behavior on the students of UINSA and is observed based on demographic elements (gender, faculty and education background). The research method was carried out with quantitative approach where data collection was carried out by distributing questionnaires referring to the UNESCO Media and Information Literacy Assessment Framework via online. The results of this research indicate that the level of student religious digital literacy behavior is on a advance level. However, in demographic element, it shows various digital literacy levels, there are those who get advanced and intermediate levels. The results of this study are expected to be a reference for university to develop digital religious literacy competencies among their students in the future.